Efektivitas Penerapan Model Pembelajaran VAK (Visualization, Audiotory, Kinesthetic) terhadap Hasil Belajar PAI dan BP di Kelas XI SMA Negeri 1 Tigo Nagari Kabupaten Pasaman - Susanti, Juli; Muliati, Indah (Lembaga Yasin AlSys, 2023)
This study aims to look at the effectiveness of applying the VAK (Visualization, Audiotory, Kinesthetic) model to the learning outcomes of PAI and BP in Class XI SMA Negeri 1 Tigo Nagari, Pasaman Regency, which in fact the teaching method used by the teacher is still monotonous and uninteresting, so students find it difficult to understand the material and have an impact on low student learning outcomes. The sampling technique in this study used purposive sampling. Methods of data collection in this study using pretest and posttest. The data in this study were analyzed using a paired sample t-test. The results showed that the control group obtained sig. (2-tailed) = 0.001 <0.05 means that H0 is rejected and Ha is accepted, and the experimental group is sig. (2-tailed) = 0.001 <0.05 means that H0 is rejected and Ha is accepted, it means that the application of the VAK (Visualization, Audiotory, Kinesthetic) learning model is effective in improving PAI and BP learning outcomes in Class XI SMA Negeri 1 Tigo Nagari, Pasaman Regency. Learning Islamic Religious Education using the VAK (Visualization, Audiotory, Kinesthetic) learning model is more effective than conventional learning models.